2011
DOI: 10.1002/iub.443
|View full text |Cite
|
Sign up to set email alerts
|

Globins in Caenorhabditis elegans

Abstract: SummaryExtensive in silico search of the genome of Caenorhabditis elegans revealed the presence of 33 genes coding for globins that are all transcribed. These globins are very diverse in gene and protein structure and are localized in a variety of cells, mostly neurons. The large number of C. elegans globin genes is assumed to be the result of multiple evolutionary duplication and radiation events. Processes of subfunctionalization and diversification probably led to their cell-specific expression patterns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The C. elegans genome encodes a variety of other neurally expressed globins that may similarly modify neural function (8). It would be interesting to investigate whether neuroglobin alters information processing in vertebrate neural circuits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The C. elegans genome encodes a variety of other neurally expressed globins that may similarly modify neural function (8). It would be interesting to investigate whether neuroglobin alters information processing in vertebrate neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…They have been proposed to metabolize reactive oxygen species (ROS), signal redox state, store O 2 , control apoptosis, and negatively regulate Gi/o signaling (7). The genome of Caenorhabditis elegans encodes an unusually large family of globins, and many are expressed in neurons (8). One of these, GLOBIN-5 (GLB-5), is expressed in the oxygen sensing neurons URX, AQR, PQR, and BAG, where it accumulates at dendritic endings (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans has 302 neuronal cells, which comprise one-third of somatic cells. Interestingly, the globin-like proteins are mainly expressed in neurons of C. elegans (10,11). It was reported that behavioral responses of C. elegans to chemicals and gases are controlled by gene activities that are mostly deployed in neurons (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In silico analysis of the genome of the free-living nematode Caenorhabditis elegans resulted in the identification of a family of 33 globin genes, labeled glb-1 to glb- 33, that are all transcribed. The encoded globins, GLB-1 to GLB-33, are localized in a specific subset of cells (2)(3)(4)(5). Characterization of some of these globins indicated that they are involved in a wide variety of cellular processes.…”
mentioning
confidence: 99%